What Has Been Trending in the Research of Polyhydroxyalkanoates? A Systematic Review - Guzik, Maciej; Witko, Tomasz; Steinbüchel, Alexander; Wojnarowska, Magdalena; Sołtysik, Mariusz; Wawak, Sławomir (Frontiers in Bioengineering and Biotechnology, 2020)
Over the past decades, enormous progress has been achieved with regard to research on environmentally friendly polymers. One of the most prominent families of such biopolymers are bacterially synthesized polyhydroxyalkanoates (PHAs) that have been known since the 1920s. However, only as recent as the 1990s have extensive studies sprung out exponentially in this matter. Since then, different areas of exploration of these intriguing materials have been uncovered. However, no systematic review of undertaken efforts has been conducted so far. Therefore, we have performed an unbiased search of up-to-date literature to reveal trending topics in the research of PHAs over the past three decades by data mining of 2,227 publications. This allowed us to identify eight past and current trends in this area. Our study provides a comprehensive review of these trends and speculates where PHA research is heading.